2010
DOI: 10.1007/s11695-010-0254-4
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Eradication Therapy in Obese Patients Undergoing Gastric Bypass Surgery—Fourteen Days Superior to Seven Days?

Abstract: A 14-days triple therapy is more effective than 7-days triple therapy suggesting this regimen should be the first-line therapy for HP eradication in Portuguese obese patients undergoing bypass gastric surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Abdullahi et al employed classic triple therapy (pantoprazole, clarithromycin, and amoxicillin for 7 days) and included overweight and individuals with obesity, while in the study of Laudanno et al they included only patients with obesity undergoing bariatric surgery, they used the quadruple concomitant regimen for 14 days, yielding equivalent ndings. Similar results have been found by Cerqueira et al [21]. Other authors, such as Pellicano R, question this relationship, suggesting a similar H pylori eradication rate in obese and the general population [22].…”
Section: Discussionsupporting
confidence: 84%
“…Abdullahi et al employed classic triple therapy (pantoprazole, clarithromycin, and amoxicillin for 7 days) and included overweight and individuals with obesity, while in the study of Laudanno et al they included only patients with obesity undergoing bariatric surgery, they used the quadruple concomitant regimen for 14 days, yielding equivalent ndings. Similar results have been found by Cerqueira et al [21]. Other authors, such as Pellicano R, question this relationship, suggesting a similar H pylori eradication rate in obese and the general population [22].…”
Section: Discussionsupporting
confidence: 84%
“…Abdullahi et al [149] showed lower rates of Helicobacter pylori eradication using a flat dose of clarithromycin 250 mg and amoxicillin 1 g three times daily with pantoprazole 40 mg twice daily in a population of obese (55%) vs. non-obese patients (85%; P ¼ 0.0059), and suggested that higher doses of antibiotics may be necessary in this group; longer durations also appear more effective [150]. Abdullahi et al [149] showed lower rates of Helicobacter pylori eradication using a flat dose of clarithromycin 250 mg and amoxicillin 1 g three times daily with pantoprazole 40 mg twice daily in a population of obese (55%) vs. non-obese patients (85%; P ¼ 0.0059), and suggested that higher doses of antibiotics may be necessary in this group; longer durations also appear more effective [150].…”
Section: Macrolidesmentioning
confidence: 99%
“…Thus, due to the presence of this bacteria in obese population undergoing Roux-en-Y bypass gastric surgery and the concern that it may exacerbate postoperative foregut symptoms and increase gastric cancer risk, this led the surgeons to adopt a policy of Hp systematic eradication preoperatively. Cerqueira et al suggested that the 14-day triple therapy (proton pump inhibitor, clarithromycin, and amoxicillin) is more effective than 7 days [27]. …”
Section: Discussionmentioning
confidence: 99%